Efficacy and Safety of Astragalus-Containing Traditional Chinese Medicine Combined With Platinum-Based Chemotherapy in Advanced Gastric Cancer: A Systematic Review and Meta-Analysis - Cheng, Mengqi; Hu, Jiaqi; Zhao, Yuwei; Jiang, Juling; Qi, Runzhi; Chen, Shuntai; Li, Yaoyuan; Zheng, Honggang; Liu, Rui; Guo, Qiujun; Zhang, Xing; Qin, Yinggang; et al. (Frontiers in Oncology, 2021)
Background Astragalus-containing traditional Chinese medicine (TCM) is widely used as adjunctive treatment to platinum-based chemotherapy (PBC) in patients with advanced gastric cancer (AGC) in China. However, evidence regarding its efficacy remains limited. This study aimed to evaluate the efficacy and safety of Astragalus-containing TCM combined with PBC in AGC treatment. Methods We searched for literature (up to July 19, 2020) in eight electronic databases. The included studies were reviewed by two researchers. The main outcomes were the objective response rate (ORR), disease control rate (DCR), survival rate, quality of life (QOL), adverse drug reactions (ADRs), and peripheral blood lymphocyte levels. The effect estimate of interest was the risk ratio (RR) or mean difference (MD) with 95% confidence intervals (CIs). Trial sequential analysis (TSA) was used to detect the robustness of the primary outcome and to calculate the required information size (RIS). Certainty of the evidence was assessed using the GRADE profiler. Results Results based on available literature showed that, compared with patients treated with PBC alone, those treated with Astragalus-containing TCM had a better ORR (RR: 1.24, 95% CI: 1.15–1.34, P < 0.00001), DCR (RR: 1.10, 95% CI: 1.06–1.14, P < 0.00001), 1-year survival rate (RR: 1.41, 95% CI: 1.09–1.82, P = 0.009), 2-year survival rate (RR: 3.13, 95% CI: 1.80–5.46, P < 0.0001), and QOL (RR: 2.03, 95% CI: 1.70–2.43, P < 0.00001 and MD: 12.39, 95% CI: 5.48–19.30, P = 0.0004); higher proportions of CD3+ T cells and CD3+ CD4+ T cells; higher ratio of CD4+/CD8+ T cells; nature killer cells; and lower incidence of ADRs. Subgroup analysis showed that both oral and injection administration of Astragalus-containing TCM increased tumor response. Whether treatment duration was ≥8 weeks or <8 weeks, Astragalus-containing TCM could increase tumor response in AGC patients. Furthermore, Astragalus-containing TCM combined with oxaliplatin-based chemotherapy could increase the ORR and DCR; when with cisplatin, it could only increase the ORR. Conclusion Current low to moderate evidence revealed that Astragalus-containing TCM combined with PBC had better efficacy and less side effects in the treatment of AGC; however, more high-quality randomized studies are warranted. Systematic Review Registration PROSPERO, identifier CRD42020203486.